TINJAUAN DESAIN INTERIOR KORIDOR HALL MALL BOEMI KEDATON DI LAMPUNG - Primayudha, Novrizal (Jurusan Seni Rupa STSI Bandung, 2018)
The interior design objects are manifestation of sign interactions as a communication system between designers who send their messages in interior architect and the observers or common people who interpret or perceive the interior architect by their own cultural background and interpretation. The focus of this research is to reveal interior elements implementation on the interior design of food court and department store at Boemi Kedaton Mall in Lampung. This observation explored all of interior signs through signs analysis and interior elements classification. Finally, the interpretation of those signs is needed to gain a corresponding interpretation, which can be regarded as an alternative of design concept that gives a new meaning to their observers.Keywords: Semiotics, Interior Architecture, Sign Analysis of Interior Architecture, Sign Meaning of Boemi Kedaton Mall Interior________________________________________________________________Objek rancangan interior merupakan manifestasi dari interaksi tanda-tanda sebagai sistem komunikasi antara desainer yang membuat pesan dalam rancangan interior bangunan dan pengamat/ masyarakat awam untuk menginterpretasi atau mempersepsikannya sesuai dengan latar belakang budaya dan tingkat pemahamannya. Fokus dari penelitian ini bertujuan untuk mengungkap penerapan elemen interior sebagai tanda pada rancangan interior food court dan department store di Mall Boemi Kedaton Lampung melalui analisa tanda dan klasifikasi elemen rancangan interiornya. Interpretasi terhadap makna tanda diperlukan untuk memperoleh sebuah kesepakatan penafsiran, sebagai sebuah usulan untuk memperoleh konsep desain yang memberikan makna baru bagi pengamatnya.Kata Kunci: Semiotika Arsitektural Interior, Analisa Tanda Arsitektural Interior, Makna Tanda pada Rancangan Interior Mall Boemi Kedaton